Enhanced thermal efficiency on mixed convection flow of TiO2 – Water nanofluid inside a double lid driven zigzag cavity with and without heated obstacles insertion - Md. Aslam Hossain; M. A. H. Sajib; Md. Sagib; Md. Rafiqul Islam; Goutam Barai; Chinmayee Podder; Bijan Krishna Saha (International Journal of Thermofluids)
This paper represents the enhancement of thermal efficiency on mixed convection flow of TiO2 – water nanofluid inside a double lid driven zigzag cavity using Galerkin's weighted residual-based finite element techniques implemented in COMSOL Multiphysics 6.2. To ensure the reliability of the obtained results, extensive comparisons and validations are conducted against relevant literatures. The flow is considered to be incompressible, laminar and steady. The top and bottom wall of the cavity are moving in the same direction with a constant velocity and the remaining walls are in no slip condition. The left vertical wall of the cavity is heated uniformly while the right vertical wall is cooled. The other walls of the cavity are well insulated. The investigation includes pertinent parametric effects of Rayleigh number(Ra), Reynolds number(Re), Richardson number(Ri) and nano-particles volume fraction(φ) and the range of the parameters are taken as 102 ≤ Ra ≤ 106, 5 ≤ Re ≤ 400, 0.1 ≤ Ri ≤ 10, and 0 ≤ φ ≤ 0.05. The velocity profiles together with temperature distributions are represented in the forms of stream functions and isotherm contours respectively whereas the heat transfer rate is calculated in terms of Nusselt number. Moreover, this study is investigated the impacts of the parameters on stream functions, isotherm contours and heat exchange inside a double lid driven cavity with and without heated circular obstacles. This analysis demonstrates that an increase in nanoparticle volume fraction enhances the heat transfer (HT) rate, with Reynolds and Richardson numbers playing a significant role in optimizing heat transfer performance within the cavity. The average Nusselt number of the cavity with circular obstacles insertion becomes almost double than the cavity without circular obstacles, in of case φ = 0.00. As φ increases, the concentration of nanoparticles increases, leading to enhanced thermal conductivity of the cavity. For a Reynolds number Re= 200 and φ = 0.05, the presence of heated obstacles increases the average Nusselt number by approximately 66.29 % compared to the case without obstacles. Similarly, at Re = 400 and φ = 0.05, the inclusion of an obstacle enclosure improves the overall thermal efficiency of the system by approximately 60.4 % compared to the absence of the obstacles.